An integer programming formulation for the music school timetabling problem - Þórhildur Gunnarsdóttir 1991- (2018)
Before every semester, music schools in Iceland face the challenge of creating timetables for students and teachers registered at the school. Many music schools create their timetables manually, which is very time consuming. In this thesis a model will be presented that is intended to solve the music school timetabling problem, assigning students and teachers to courses and classrooms. This project is done in cooperation with the music school Tónmenntaskóli Reykjavíkur which is located in Reykjavík. The assignment process at Tónmenntaskóli Reykjavíkur is currently done manually. Before the assignment process starts the school gathers data and information from every teacher and student regarding their availability and wishes for the semester. Tónmenntaskóli Reykjavíkur has agreed to share this information and provide the required data needed to create the model. The main goal of the project is to create an optimization model which automates the assign- ment process, ensuring that students and teachers are assigned to right courses considering their preferences and trying to grant all wishes for the semester. The automation should min- imize the scheduling time and reduce possible errors that may occur when done manually. The results show that an integer programming model with a two phase model approach can be used to solve the music school timetabling problem, creating a feasible schedule for a music school were students and teachers are assigned to right courses. Fyrir hvert skólaár standa starfsmenn tónlistarskóla á Íslandi frammi fyrir krefjandi verkefni, að búa til stundatöflur fyrir nemendur sína og kennara, raða kennurum og nemendum niður á námskeið og skólastofur. Flestir tónlistarskólar í dag útbúa stundatöflurnar sínar handvirkt sem er krefjandi og tímafrekt. Í þessari ritgerð verður sett fram stærðfræðilíkan sem gæti hjálpað starfsmönnum tónlistarskóla við gerð þessara stundataflna. Stundaskráargerð Tónmenntaskóla Reykjavíkur, tónlistarskóli staðsettur í ...